Ethnomathematics in Aceh Coastal Children's Football Game - Wahyuni; Siti Habsari Pratiwi (Universitas Pendidikan Ganesha, 2023)
Each culture has its own mathematics, and mathematics is born of culture. And ethnomathematics exists as a link between mathematics and culture. This study aims to analyze the ethnomathematics contained in the soccer game of Aceh's coastal children. This type of exploratory research uses an ethnographic approach. The subjects in this study were Acehnese coastal children aged five to twelve years who were playing ball in the afternoon, totaling 18 people. The selection of the subject of the study was carried out using the incidental sampling technique. Data collection is carried out through observation, interviews, and documentation. There are four forms of data analysis in this study such as domain, taxonomic, component, and cultural themes. The results of this study show that children, while playing, have used knowledge in mathematics, such as the concepts of line alignment, addition and difference, comparison, the theory of opportunity, numbers and rounding, and measurement, without realizing it. In addition, the mathematical concepts used in football games show that Acehnese coastal children have their own ethnomathematics, as evidenced by their being able to do mathematical modeling, understand the concept of harmony, and argue. So that ethnomathematics in the soccer game of Aceh coastal children is shown in the form of mathematical behavior that reflects children's understanding of problems and how to solve them using mathematics.